To solve the system by elimination, we can multiply the second equation by 3 to make the coefficients of x in both equations the same.
Original system:
3x − 3y = 1
x − y = 15
Multiply the second equation by 3:
3(x − y) = 3(15)
3x − 3y = 45
Now the system becomes:
3x − 3y = 1
3x − 3y = 45
Subtract the first equation from the second equation:
(3x − 3y) − (3x − 3y) = 45 − 1
0 = 44
This equation is contradictory and cannot be true. Therefore, the system is inconsistent and has no solution.
Solve the system by elimination.
3x−3y=1
x−y=15
1 answer